Cohort profile: Design and implementation of the Danish Physiotherapy Research Database for patients receiving primary care with chronic disease - Erhard Næss-Schmidt; Nils-Bo de Vos Andersen; David Høyrup Christiansen; Jørgen Feldbæk Nielsen; Peter William Stubbs (BMJ Open)
Purpose Free of charge physiotherapy (FCP) is free physiotherapy provided by the Danish government for patients with a range of chronic diseases. To date, the population has not been described in depth making evaluation and decision making difficult. The purpose of this study was to (1) describe the development and the content of a novel clinical physiotherapy database for FCP (PhysDB-FCP) and (2) present the cohort profile based on the data collected.Participants Ninety-nine clinics (17 460 FCP patients) were invited to participate in the development process from 2018 to 2019. Eleven clinics consented (2780 FCP patients) and 534 patients performed the physiotherapy assessment using the PhysDB-FCP tool, with 393/534 completing the patient survey.Findings to date The content of the PhysDB-FCP was developed through an iterative process involving consensus between clinical and research workgroups. Prior to using the tool all consenting sites received training to use/administer the tool. All data were collected/stored using the PhysDB-FCP. Items finally chosen for the PhysDB-FCP included demographic information, questions about health status and daily functioning, functional tests, treatment plan and validated questionnaires. The initial patient cohort composed of 63.4% women with main diagnoses of multiple sclerosis (22.7%) and Parkinson’s disease (17.0%). The ability to perform personal/instrumental activities of daily living and functional ability varied widely. Other non-physiotherapy related issues were identified in numerous patients (ie, 34.9% of patients were at risk of depression) and multidisciplinary interventional approaches could be considered.Future plans The current study has provided a comprehensive description of patients receiving FCP, using data collected from the novel PhysDB-FCP. Collected information can be used to facilitate microlevel to macrolevel programme evaluation and decisions. Although the PhysDB-FCP is promising, the tool requires optimisation before it is implemented regionally and/or nationally.